2011
DOI: 10.1371/journal.pone.0016455
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial T16189C Polymorphism Is Associated with Coronary Artery Disease in Middle European Populations

Abstract: BackgroundThe pivotal role of mitochondria in energy production and free radical generation suggests that the mitochondrial genome could have an important influence on the expression of multifactorial age related diseases. Substitution of T to C at nucleotide position 16189 in the hypervariable D-loop of the control region (CR) of mitochondrial DNA (mtDNA) has attracted research interest because of its suspected association with various multifactorial diseases. The aim of the present study was to compare the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 38 publications
3
59
0
4
Order By: Relevance
“…Additionally, the results agreed with the next following research in nucleotide behaviors that may be related to strength of the chemical bonds in spite of different area investigations also some of them called guanine an ancestral nucleotide as the most conserved nucleotide [51][52][53][54].…”
Section: Estimation Of Transition/transversion Matrix By Maximum Compsupporting
confidence: 86%
“…Additionally, the results agreed with the next following research in nucleotide behaviors that may be related to strength of the chemical bonds in spite of different area investigations also some of them called guanine an ancestral nucleotide as the most conserved nucleotide [51][52][53][54].…”
Section: Estimation Of Transition/transversion Matrix By Maximum Compsupporting
confidence: 86%
“…It was reported that a T-C transition (termed as T16189C) occurred in ~30% of Asian people (24), forming a poly-C structure, which was reported to be a disease association research hotspot (25). However, no significant difference was identified in the frequency of T16189C between patients with AML and the controls (32.3 vs. 37.7%; P=0.324), as presented in Table IV.…”
Section: Association Between Mtdna D-loop Variations and Aml Riskmentioning
confidence: 91%
“…The mitochondrial haplogroup [43] and CR polymorphism [29] data were obtained from previous studies.…”
Section: Methodsmentioning
confidence: 99%